QUALITY OF SERVICE IN MAKING KTP AND KK IN SURADE SUBDISTRICT, SUKABUMI REGENCY - Aldi Apriana Siswandi; M. Rijal Amirulloh; Andi Mulyadi (DIA: Jurnal Administrasi Publik, 2023)
The government in implementing public services must improve the quality of services and ensure the provision of optimal public services. The problem phenomenon focuses on the not optimal quality of service in terms of errors in writing KTP and KK identities, the absence of blanks, the lack of optimal human resources, resulting in human erorr. Thet eori used by Zeithhaml Parasuraman Barry (2011) include Physical evidence, Reliability, Assurance and Empathy. The research method uses observation, interviews, and documentation. The research instrument is purposive sampling. The analysis unit and the informant's setting used snowball sampling. Data validation using triangulation, data analysis using data condensation, data view, and drawing conclusion. With tangible results, it has been felt well by the people of Surade District. Based on the reliability of the service unit's ability to provide the promised service immediately and satisfactorily for service users is still not well felt and the Responsive Dimension is still not well implemented. in conclusion Service standards in District Offices Surade has been implemented in accordance with applicable procedures, but the quality of service provided is still not good because the officers who provide waiters are not friendly so they do not provide comfort for service users at the Surade District Office, Sukabumi Regency.